Effects of Inclusion on Inclusion Front Tensile Stress - Norasethasopon, Somchai (Asian Health, Science and Technology Reports, 2013)
The purpose of this research was to investigate the effect of inclusion on inclusion front tensile stress during copper shaped-wire drawing. The effect of inclusion length on copper shaped-wire drawing was investigated. The deformations and the mean normal stress (σm) of copper shaped-wires that contain an inclusion were calculated by two-dimensional finite elemental analysis. As the FEA results, while the inclusion passed through the die, the neck due to inclusion wire drawing occurred on some parts of copper wire surface in front of and near the leading edge of the inclusion. The effect of inclusion length (Li/Do) on tensile stress in front of inclusion during copper shaped-wire drawing was carried out. For Li/Do > 1.0 the inclusion length did not effect on inclusion front tensile stress. In case of 1 > Li/Do > 0.2 and Li/Do < 0.2, inclusion length slightly and strongly influences on inclusion front tensile stress, respectively.